2013
DOI: 10.1172/jci70355
|View full text |Cite
|
Sign up to set email alerts
|

p53 isoforms regulate aging- and tumor-associated replicative senescence in T lymphocytes

Abstract: Cellular senescence contributes to aging and decline in tissue function. p53 isoform switching regulates replicative senescence in cultured fibroblasts and is associated with tumor progression. Here, we found that the endogenous p53 isoforms Δ133p53 and p53β are physiological regulators of proliferation and senescence in human T lymphocytes in vivo. Peripheral blood CD8 + T lymphocytes collected from healthy donors displayed an age-dependent accumulation of senescent cells (CD28 -CD57 + ) with decreased Δ133p5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
144
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(154 citation statements)
references
References 59 publications
7
144
0
Order By: Relevance
“…To examine whether p53 isoforms Δ133p53 and p53β are expressed in the human brain, immunofluorescence staining using Δ133p53-specific antibody MAP4 and p53β-specific antibody TLQ40 30,31 was performed in non-disease human brain tissues (Supplementary Table S1). The specificity of the isoform-specific antibodies in immunofluorescence staining was confirmed using a p53-null cell line H358 with a Δ133p53, full-length p53, or p53β expression vector (Supplementary Figures S1A and B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To examine whether p53 isoforms Δ133p53 and p53β are expressed in the human brain, immunofluorescence staining using Δ133p53-specific antibody MAP4 and p53β-specific antibody TLQ40 30,31 was performed in non-disease human brain tissues (Supplementary Table S1). The specificity of the isoform-specific antibodies in immunofluorescence staining was confirmed using a p53-null cell line H358 with a Δ133p53, full-length p53, or p53β expression vector (Supplementary Figures S1A and B).…”
Section: Resultsmentioning
confidence: 99%
“…29 Δ133p53, an N-terminal truncated isoform, functions as a negative regulator of cellular senescence by dominant-negatively inhibiting full-length p53. 30,31 p53β, a C-terminal modified isoform, functions as a co-activator of full-length p53 to promote senescence. 30,31 In this study, we report that Δ133p53 and p53β regulate the neuroprotective and neurotoxic functions of human astrocytes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mondal et al . (2013) reported that alternative dominant‐negative p53 splicing forms, namely Δ133p53 and p53β, are central players during in vitro and in vivo induced human T‐cell senescence. p53β overexpression or ∆133p53 down‐regulation represses CD28 gene transcription in human cells (Mondal et al ., 2013).…”
Section: Cellular Senescence and Immune Cell Fate Decisionmentioning
confidence: 99%
“…(2013) reported that alternative dominant‐negative p53 splicing forms, namely Δ133p53 and p53β, are central players during in vitro and in vivo induced human T‐cell senescence. p53β overexpression or ∆133p53 down‐regulation represses CD28 gene transcription in human cells (Mondal et al ., 2013). Accordingly, forced expression of ∆133p53 or CD28 in CD8 + CD28 null human T cells is sufficient to delay telomere‐dependent growth arrest following culture exhaustion, but failed to permanently prevent the process (Parish et al ., 2010).…”
Section: Cellular Senescence and Immune Cell Fate Decisionmentioning
confidence: 99%